The Clinical Study on Bell's Palsy Patients with TCD Measurement - Lee Hyun; Lee Byung-ryul; Ann Taek-won (Korean Pharmacopuncture Institute, 2003)
Objective : This study was carried to make out the connection between cerebral artery blood flow velocity and ischemic theory that presumed the cause of Bell's palsy. Method : We measured cerebral artery blood flow velocity each external carotid artery, internal carotid artery, common carotid artery, siphon, superficial temporal artery by TCD to 20 patients who diagnosed as facial nerve palsy from march 2001 to July 2001 and all objectives devided two groups as palsy side. A group is right side facial nerve palsy and B group is left facial nerve palsy. Results : 1. There is no effective change of blood flow in external carotid artery either A, B group. 2. There is no effective change of blood flow in internal carotid artery either A, B group. 3. There is no effective change of blood flow in common carotid artery either A, B group. 4. There is no effective change of blood flow in siphon artery either A, B group. 5. There is no effective change of blood flow in superficial temporal artery either A, B group.